2007
DOI: 10.1002/erv.836
|View full text |Cite
|
Sign up to set email alerts
|

Body image disturbance in young North European and East Asian women with and without eating disorders in Australia and in Singapore

Abstract: Socio-cultural factors other than body image may play more important roles in SC women's ED psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
2
19
1
Order By: Relevance
“…The EDE-Q subscale scores in our study were similar to those found in earlier studies, (11,13) which may imply that there was a consistent trend from 2007 to 2012 for body image concerns and eating psychopathology in our local population.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The EDE-Q subscale scores in our study were similar to those found in earlier studies, (11,13) which may imply that there was a consistent trend from 2007 to 2012 for body image concerns and eating psychopathology in our local population.…”
Section: Discussionsupporting
confidence: 90%
“…The profile of participants in our study was also similar to the Singapore arm of studies by Soh et al (11,13) in terms of gender and ethnicity distributions, and average age and BMI at presentation, suggesting that the demographic characteristics of new presentations have not shifted much over the years. Although these studies had a small sample size of Singaporean Chinese patients, they were the only local studies with which we could compare our cohort.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…1,2 Thus, findings from recent studies suggest that levels of body dissatisfaction, preoccupation with thinness, and other aspects of eating-disordered behavior in ''newly industrialized'' Asian nations, such as Hong Kong, Singapore, and Taiwan, may be as high as, if not higher than, those observed in Western nations. [3][4][5][6][7][8] However, evidence concerning the prevalence and presentation of eating-disordered behavior in these regions remains limited in several respects. For one thing, much of the research involves case series of patients receiving specialist treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Soh et al 7,8 compared eating disorder psychopathology between Singaporean women and Australian women using the Eating Disorder Examination Questionnaire (EDE-Q), 23 a measure that provides for the assessment of both attitudinal features and the occurrence and frequency of specific eating disorder behaviors. 23,24 As in other studies, Soh and colleagues found high levels of eating disorder psychopathology in Singaporean women higher than those of both Australian women and expatriate Singaporeans.…”
Section: Introductionmentioning
confidence: 99%